The more the better? Cumulative issue ownership and intra-campaign party switching. (April 2020) - Petitpas, Adrien; Sciarini, Pascal
Abstract: We contribute to the literature on short term changes in voters' party preferences (or intra-campaign party switching), by advancing a factor that has been neglected so far: Voters' perceptions about parties' issue competence. We develop a model of party switching that includes both classic predictors and issue ownership considerations. Moreover, in contrast to the usual single issue ownership conception focusing on the party deemed most competent to solve the most important problem, we argue that voters base their party choice on their perceptions of parties' competence on a variety of issues, i.e. on cumulative issue ownership. We test our model on panel data from the 2015 Swiss election study. The change in competence perceptions appears as a strong predictor of party switching: The higher the increase in the number of issues on which voters see a party as most competent during the campaign, the higher their likelihood to switch to that party.